(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The faunistical inventory of the Spiders was studied during seven years in the Paris Basin (Gâtinais). This study was carried out in large fields managed in short rotation (maizewheat and dicotyledonous-wheat) with pitfall traps and yellow water traps. The data collected by trapping revealed the diversity and relative abundance of the Spiders. The autors give the list of 104 species which were inventoried. The main families are Erigonidae and Linyphiidae, but 15 others are noticed in this work. Some species must be pointed out: Oedothorax apicatus, Lepthyphantes tenuis and Erigone atra for their abundance; Milleriana inerrans generaly rare, but which has been catched almost constantly, Entelecara graeca unknown in cereal biocenosis before 1984 whose the abundance is notable.